(NpOWESTI(B. (NrASSKAZY (B/s - (NdOSTOEWSKIJ(B, (NfEDORs ((NmOSKWA(B:s (NpRAWDA(B,s, 1985)
(Nw SBORNIK WO[LI IZBRANNYE POWESTI I RASSKAZY IZWESTNOGO RUSSKOGO PISATELQ f(B.(Nm(B. (NdOSTOEWSKOGO(B: (NPOWESTX (B"(NzAPISKI IZ PODPOLXQ(B", (NRASSKAZY (B"(NwE^NYJ MUV(B", "(NmALX^IK U hRISTA NA ELKE(B", "(NsTOLETNQQ(B", "(NkROTKAQ(B" (NI FANTASTI^ESKIJ RASSKAZ (B"(NsON SME[NOGO ^ELOWEKA(B".s
rus
Keywords: (NpOWESTI I RASSKAZYs